PENGARUH PERBANDINGAN JAGUNG MANIS DAN EDAMAME TERHADAP KARAKTERISTIK SUSU JAGUNG MANIS EDAMAME - Larosta, Jeany Tio; Permana, I Dewa Gde Mayun; Sugitha, I Made (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 8 No 4 (2019): Jurnal ITEPADO - 10.24843/itepa.2019.v08.i04.p06, 2019)
This study aimed to determine effect of ratio sweet corn and edamame to characteristic of sweet corn edamame milk, also to know the best ratio from sweet corn and edamame to produce the best characteristic of sweet corn edamame milk. The experimental design used was completely randomized design with different ratio of sweet corn and edamame which consist by 5 level : 300:0, 250:50, 200:100, 150:150, and 100:200. The treatment was repeated 3 times to obtain 15 experimental units. The result of the research show that ratio of sweet corn and edamame had very significant effect on total solid, fat content, protein content, calcium content, viscosity, scoring test, and had no significant effect  panelist preference for color, flavor, taste, and overall acceptance. Ratio 150:150 (P3) is the best treatment that produced sweet corn edamame milk with total solid 12.36%, fat content 6.34%, protein content 3.70%, calcium content 243.19 mg/L, and viscosity 613.33 cps. The result for sensory test color is yellowish green (liked), flavor is typical edamame (rather liked), taste is typical edamame (rather liked), and overall acceptance is rather liked. Keywords : sweet corn, edamame, corn milk